Land Holding and Livelihoods: A Synthesis from Modi Khola Watershed, Nepal - Rijal, Shiba Prasad (The Third Pole: Journal of Geography Education, 2009)
This paper is an attempt to analyze land holding pattern and its consequences in rural livelihoods especially of Modi Khola watershed located in Western Development Region, Nepal. The study is mainly based on primary data collected from 360 households selected randomly from Modi Khola watershed during September-October, 2002. Land is an important natural asset, has greater implications on people's livelihoods. The distribution of land among households is uneven in this area. The implications of unequal distribution and access of land can clearly be seen on household income as well as level of food sufficiency. The average household income increases with the increase in land holding size. Likewise, the percentage of household reporting sufficient food production for household consumption increases with land holding size. Thus, the well-being of local people is largely tied-up with amount of land owned by the household. DOI: http://dx.doi.org/10.3126/ttp.v5i0.1952 The Third Pole, Vol. 5-7, PP 43-51:2007